2012
DOI: 10.1007/s10535-012-0057-7
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of peanut acyl carrier protein in tobacco alters fatty acid composition in the leaf and resistance to cold stress

Abstract: Acyl carrier protein (ACP), as an essential protein cofactor, plays an important role in de novo synthesis of fatty acids in plastids. In this study, the expression profile of peanut (Arachis hypogaea) AhACP1-1 and AhACP1-2 was analyzed in different tissues. The expression level of AhACP1-1 was highest in the seed, whereas expression was barely detected in the shoot, and AhACP1-2 was expressed in every tissue analyzed with the highest expression level detected in the leaf and seed. Overexpression (OE) and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
0
25
0
1
Order By: Relevance
“…[121][122][123] A number of chemotherapy drugs exert stress on the cancer genome, most of which act as genotoxicants that damage the DNA and induce the DDR; these include DNA cross-linkers, topoisomerase poisons, and alkylating agents. [124][125][126] Although conventional anticancer agents were developed to selectively target highly proliferative cancer cells over normal cells, highly proliferative normal tissues (e.g. bone marrow, gut epithelium) are also targeted, and the side effects can sometimes be life-threatening.…”
Section: Genotoxic Stressmentioning
confidence: 99%
“…[121][122][123] A number of chemotherapy drugs exert stress on the cancer genome, most of which act as genotoxicants that damage the DNA and induce the DDR; these include DNA cross-linkers, topoisomerase poisons, and alkylating agents. [124][125][126] Although conventional anticancer agents were developed to selectively target highly proliferative cancer cells over normal cells, highly proliferative normal tissues (e.g. bone marrow, gut epithelium) are also targeted, and the side effects can sometimes be life-threatening.…”
Section: Genotoxic Stressmentioning
confidence: 99%
“…Recent studies have shown that the light signaling gene phyB also participates in a pathway that promotes resistance to chilling . PhyB negatively regulates chloroplast structural stability by lowering levels of unsaturated fatty acids present in membrane lipids . PhyB deficiency positively regulates OsPIL16 and OsDREB1 , thereby alleviating chilling‐induced photoinhibition and enhancing chilling tolerance .…”
Section: Temperature Changesmentioning
confidence: 99%
“…[135][136][137] PhyB negatively regulates chloroplast structural stability by lowering levels of unsaturated fatty acids present in membrane lipids. [138][139][140] PhyB deficiency positively regulates OsPIL16 and OsDREB1, 141 thereby alleviating chilling-induced photoinhibition and enhancing chilling tolerance. [142][143][144] Similar mechanisms have also been characterized in Suaeda salsa.…”
Section: Salt Stressmentioning
confidence: 99%
“…Plants can detect various environmental signals such as high salt concentration (Shen et al, 2014;Wang S. et al, 2014;Sui et al, 2017), cold temperature (Tang et al, 2012;Liu et al, 2013;Zhao X. et al, 2014;, reactive oxygen species levels (Li K. et al, 2012), waterlogging (Song et al, 2011;Chen et al, 2016;, phosphate scarcity , and ultraviolet (UV) radiation Deng et al, 2015). Failure to appropriately respond to these stressors decreases plant productivity and affects human food and animal feed supplies.…”
Section: Introductionmentioning
confidence: 99%